Focus on Adoptive T Cell Transfer Trials in Melanoma - Liat Hershkovitz; Jacob Schachter; Avraham J. Treves; Michal J. Besser (Clinical and Developmental Immunology)
Adoptive Cell Transfer (ACT) of Tumor-Infiltrating Lymphocytes (TIL) in combination with lymphodepletion has proven to be an effective treatment for metastatic melanoma patients, with an objective response rate in 50%–70% of the patients. It is based on the ex vivo expansion and activation of tumor-specific T lymphocytes extracted from the tumor and their administration back to the patient. Various TIL-ACT trials, which differ in their TIL generation procedures and patient preconditioning, have been reported. In the latest clinical studies, genetically engineered peripheral T cells were utilized instead of TIL. Further improvement of adoptive T cell transfer depends on new investigations which seek higher TIL quality, increased durable response rates, and aim to treat more patients. Simplifying this therapy may encourage cancer centers worldwide to adopt this promising technology. This paper focuses on the latest progress regarding adoptive T cell transfer, comparing the currently available protocols and discussing their advantages, disadvantages, and implication in the future.